2013
DOI: 10.1007/s10384-013-0277-1
|View full text |Cite
|
Sign up to set email alerts
|

Five-year postoperative outcomes of apodized diffractive multifocal intraocular lens implantation

Abstract: The apodized diffractive multifocal IOL provides good, stable distance and near visual acuity levels over a 5-year follow-up period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…To that end, a further refractive procedure is required such as multifocal intraocular lens (IOL) implantation. With the continuous renewal and improvement of surgical equipment and implantation material, multifocal IOL implantation after cataract surgery has been increasingly applied in clinical practice and effectively restored visual acuity, thus becoming an alternative of refractive procedure [2][3][4][5][6][7]. Recently, some studies have shown that the multifocal IOL implantation could be safely and efficiently used for patients who had previously undergone corneal refractive laser surgery [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…To that end, a further refractive procedure is required such as multifocal intraocular lens (IOL) implantation. With the continuous renewal and improvement of surgical equipment and implantation material, multifocal IOL implantation after cataract surgery has been increasingly applied in clinical practice and effectively restored visual acuity, thus becoming an alternative of refractive procedure [2][3][4][5][6][7]. Recently, some studies have shown that the multifocal IOL implantation could be safely and efficiently used for patients who had previously undergone corneal refractive laser surgery [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Following cataract removal, the implantation of intraocular lenses that offer simultaneous near and distance vision correction is now routine. 1 …”
Section: Introductionmentioning
confidence: 99%
“…Multifocal IOLs generate different foci to overcome visual limitations at near and intermediate distances that occur with classic monofocal IOLs. Multifocal IOLs provide good distance and near functional vision without requiring corrective lenses [5678]. However, some optical side effects have been reported, including decreased contrast sensitivity (CS), glare disability, and halos [391011], which can significantly affect visual performance and patient satisfaction.…”
mentioning
confidence: 99%